Quantifying Light Response of Leaf-Scale Water-Use Efficiency and Its Interrelationships With Photosynthesis and Stomatal Conductance in C3 and C4 Species - Ye, Zi-Piao; Ling, Yu; Yu, Qiang; Duan, Hong-Lang; Kang, Hua-Jing; Huang, Guo-Min; Duan, Shi-Hua; Chen, Xian-Mao; Liu, Yu-Guo; Zhou, Shuang-Xi (Frontiers in Plant Science, 2020)
Light intensity (I) is the most dynamic and significant environmental variable affecting photosynthesis (An), stomatal conductance (gs), transpiration (Tr) and water-use efﬁciency (WUE). Currently, studies characterizing leaf-scale WUE–I responses are rare and key questions have not been answered. In particular, (1) What shape does the response function take? (2) Are there maximum intrinsic (WUEi; WUEi-max) and instantaneous WUE (WUEinst; WUEinst-max) – at the corresponding saturation irradiances (Ii-sat and Iinst-sat)? This study developed WUEi–I and WUEinst–I models sharing the same nonasymptotic function with previously published An–I and gs–I models. Observation-modelling intercomparison was conducted for field-grown plants of soybean (C3) and grain amaranth (C4) to assess the robustness of our models versus the non-rectangular hyperbola models (NH models). Both types of models can reproduce WUE–I curves well over light-limited region. However, at light-saturated region, NH models overestimated WUEi-max and WUEinst-max and cannot return Ii-sat and Iinst-sat due to its asymptotic function. Moreover, NH models cannot describe the down-regulation of WUE induced by high light, on which our models described well. The results showed WUEi and WUEinst increased rapidly within low range of I, driven by uncoupled photosynthesis and stomatal responsiveness. Initial response rapidity of WUEi was higher than WUEinst because the greatest increase of An and Tr occurred at low gs. C4 species showed higher WUEi-max and WUEinst-max than C3 species – at similar Ii-sat and Iinst-sat. Our intercomparison highlighted larger discrepancy between WUEi–I and WUEinst–I responses in C3 than C4 species, quantitatively characterizing an important advantage of C4 photosynthetic pathway – higher An gain but lower Tr cost per unit of gs change. Our models can accurately return the wealth of key quantities defining species-specific WUE–I responses – besides An–I and gs–I responses. The key advantage is its robustness in characterizing these entangled responses over a wide I range from light-limited to light-inhibitory light intensities, through adopting the same analytical framework and the explicit and consistent definitions on these responses. Our models are of significance for physiologists and modelers – and also for breeders screening for genotypes concurrently achieving maximized photosynthesis and optimized WUE.